Ṣaḥīfa-yi Sajjādiyya bā tarjumaʾī kuhan bih Fārsī - al-Sajjād, ʿAlī b. al-Ḥusayn, (Miras Maktoob, ISBN: 9789004365452., 2019)
The Ṣaḥīfa Sajjādiyya is a compilation of supplicatory prayers ascribed to the fourth Imam of the Shīʿa, ʿAlī b. al-Ḥusayn al-Sajjād (d. 94/712-13 0r 95/713-14). Alternatively referred to as the 'psalms' ( zabūr ) or the 'gospels' ( injīl ) of the family of the Prophet, the Ṣaḥīfa Sajjādiyya ranks among the holiest books of the Shīʿa, together with the Qurʾān and ʿAlī b. Abī Ṭālib's Nahj al-balāgha . Al-Sajjād was known for his piety and for his being given to prayer. Yet it is more likely that the Ṣaḥīfa is a later compilation of prayers attributed to him. The Ṣaḥīfa published here in facsimile is the 'complete' ( kāmila ) recension ascribed to Ibn Makkī (d. 786/1384) in a copy made just five years after Makkī's death, together with an early interlinear Persian translation. Apart from the orthographical and linguistic points of interest of this manuscript, its early dating may throw light on the history of transmission of Ibn Makkī's recension.